2015
DOI: 10.1016/j.jfs.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Finance and growth: Time series evidence on causality

Abstract: Please cite this article as: Oana Peia, Kasper Roszbach, Finance and growth: time series evidence on causality, Journal of Financial Stability (2014), http://dx. AbstractThis paper re-examines the empirical relationship between financial and economic development while (i) taking into account their dynamics and (ii) differentiating between stock market and banking sector development. We study the cointegration and causality between finance and growth for 22 advanced economies. Our time series analysis suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 82 publications
(125 reference statements)
1
31
1
1
Order By: Relevance
“…11 There is little controversy between them regarding the limited presence of causality directed from credit depth to growth. However, in a sharp contrast to Peia and Roszbach (2014), this paper finds only negligible evidence for the causality running from growth to credit depth.…”
Section: Figurecontrasting
confidence: 89%
See 1 more Smart Citation
“…11 There is little controversy between them regarding the limited presence of causality directed from credit depth to growth. However, in a sharp contrast to Peia and Roszbach (2014), this paper finds only negligible evidence for the causality running from growth to credit depth.…”
Section: Figurecontrasting
confidence: 89%
“…The findings of the paper can also be placed into the context of the literature that examines causality between financial structure and growth. Unlike Peia and Roszbach (2014), I assess causal relationships between credit depth and growth, omitting the potential impact of stock market development for data availability reasons. 11 There is little controversy between them regarding the limited presence of causality directed from credit depth to growth.…”
Section: Figurementioning
confidence: 99%
“…Otherwise, stock markets are more supportive for growth. The results of Peia and Rozsbach () also suggest that banks and stock markets influence economic growth differently.…”
Section: Multivariate Meta‐regressionmentioning
confidence: 96%
“…However, the differences in the effectiveness of financial structures on economic growth suggests that there may be other factors that can affect this relationship, such as the institutional development of the country. For example, recent research has shown support for stock market development particularly for highly developed countries with strong institutions (Peia and Roszbach 2015). Furthermore, it is also suggested that advanced economies benefit more from market-based financial systems compared to less-developed countries, where bank-based financial systems affect growth more effectively due to lack of access to finance (Cull and Xu 2013).…”
Section: Role Of Finance and Institutions In Economic Growthmentioning
confidence: 99%